Impacts des changements de l’occupation du sol et des changements climatiques sur le bassin versant de la rivière Davo, Côte d’Ivoire - Touao Kah Martine Gauze; Kouamé Yao Morton; Mélèdje N’diaye Hermann; Sékongo Guénolé Largaton; Soro Gnéneyougo Emile (European Scientific Journal, ESJ, 2018)
The main objective of this study is to asssess the impacts of climate change and land cover change on the hydrology of the Davo river basin located in southwestern of Côte d'Ivoire. Two scenarios of climate change (A2 and B2) and two scenarios of land cover called scenario 1 (deforestation) and scenario 2 (reforestation) were established, and streamflows under these scenarios were simulated by the hydrological model CEQUEAU. Each scenario showed distinct variations in streamflows. Regarding the impacts of land cover change, scenario 1 and scenario 2 indicate increases of 10.6% and 1%, respectively. As for the impacts of climate change, climate models predict a very wide range of possible changes in streamflows. The multimodel approach indicates a decrease in streamflows of 0.5% and 2.75% respectively under the A2 and B2 scenarios by 2050. By 2080, streamflows would increase by 14.75% under the scenario A2 and 3.5% under scenario B2. In order to implement adaptation and mitigation strategies, Representative Concentration Pathways (RCP) scenarios should be used, regional climate models should be applied, and combined assessments of the impacts of climate change and land cover should be made.